Factors Influencing Delayed Treatment in Patients With Breast Cancer During COVID-19 Pandemic - He, Shengdong; Wang, Yanlin; Zhao, Xiaoting; Xu, Fangying; Li, Juncheng; Huang, Tao; Sun, Peng; Li, Lingfan; Ai, Xiang; Xiao, Hualin; Xue, Gang; He, Siyi (Frontiers in Public Health, 2022)
Background: The outbreak of coronavirus disease 2019 (COVID-19) has endangered human health and life. This pandemic has changed people’s lifestyle and affected the regular delivery of standard cancer treatment. In the present study, we aimed to explore the influencing factors of delayed treatment in patients with breast cancer during COVID-19 pandemic. Methods: This study was a cross-sectional investigation, and the subjects were patients who were discharged from the department of burn and plastic surgery after February 2020. All participants completed this study’s online questionnaire based on the WeChat and Wenjuanxing platforms. Levels of anxiety and depression were measured by the Hospital Anxiety and Depression Scale (HADS). Patients were divided into a delay group and non-delay group according to the occurrence of delayed treatment. Univariate analysis was performed by using the t test or chi-square test. A logistic regression model was employed to determine factors associated with delayed treatment. Results: The present study included a total of 397 patients with breast cancer, among whom delayed treatment occurred in 76 patients, accounting for 19.1%. Scores on both the anxiety subscale and depression subscale in delay group were significantly higher than those in non-delay group. Compared with non-delay group, we found that patients in delay group usually had a higher level of education (P=0.020), worse self-feeling (P=0.030), poor compliance of medical order (P=0.042), and a higher prevalence of anxiety (P=0.004) and depression (P=0.012). Traffic inconvenience was also an important relevant factor for delayed treatment (P=0.001). The prevalence of recurrence in delay group was higher than that in non-delay group (P=0.018). By using logistic multivariate regression analysis, the results revealed that level of education and traffic inconvenience were independent factors influencing delayed treatment in patients with breast cancer during COVID-19 pandemic. Conclusion: The prevalence of delayed treatment in patients with breast cancer during COVID-19 pandemic is relatively high. Our findings reveal several influencing factors closely associated with delayed treatment, which is useful information that will be beneficial for patients to receive standardized therapy by taking targeted measures.